KEDUDUKAN DAN TANGGUNGJAWAB PRESIDEN DALAM SISTEM PRESIDENSIAL DI INDONESIA - Moh Hudi (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2018)
The Government system greatly determines the position and responsibility of the president. Even in the same system of government, the president’s position and responsibility may change, depending on The Rule of Law in a particular country. The position and responsibility of the president in the presidential system in Indonesia has change several times. This can be seen before and after the amandement. President in presidential System as Head of Government and Head of State. So that the president has broad authority. The president is not responsible to the parliament, because institutionally the parliament is not higher than the president as the chief executive, but is responsible to the people as voters.